RESVERATROL AND LORATADINE EFFECTS ON OXIDATIVE STRESS INDUCED BY EXPERIMENTAL INFLAMMATION - MITREA, Daniela-Rodica; CLICHICI, Simona; FILIP, Adriana; OLTEANU, Diana; BÂLDEA, Ioana; MOLDOVAN, Remus; DECEA, Nicoleta; HOTEIUC, Oana-Alina (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Resveratrol is a polyphenol with important antioxidant and anti-inflammatory roles. Loratadine, as a selective inverse-agonist of peripheral receptor H1, is described as an anti-allergic substance with potential anti-inflammatory effects. We aimed to assess the protective capacity of loratadine against oxidative stress produced by inflammation with carrageenan in comparison with a well-known antioxidant compound, resveratrol. Our results showed that resveratrol and loratadine had no protective anti-inflammatory effects in inflamed skin. As expected, resveratrol had antioxidant effects in serum and in liver. Loratadine developed oxidative stress in tegument and serum. In this experimental model, our results do not sustain the initial hypothesis that loratadine could have a protective effect in inflammation, and, on the other hand, is capable of increasing it, by producing an oxidative stress.